Specific Growth Rate (SGR), Feed Conversion Ratio (FCR), and Survival Rate (SR) of Nile tilapia (Oreochromis niloticus) fed probiotics (Probio-7) with different concentrations - sarmin, Sarmin; Setyastuti, Aryanti Indah; Yudistira, Denny indra; Prasetyo, Dwi Yanuar Budi (Universitas Malikussaleh, 2025)
This study aims to examine the effect of probiotic (Probio-7) supplementation on the Specific Growth Rate (SGR), Feed Conversion Ratio (FCR), and Survival Rate (SR) of Nile tilapia (Oreochromis niloticus). The research was conducted from January to March 2025 at the UNU Purwokerto Laboratory. An experimental method was used with a completely randomized design (CRD), consisting of 4 treatments and 3 replications. The treatments were: P1 (feed without probiotics), P2 (feed with 8 ml/kg probiotic), P3 (feed with 10 ml/kg probiotic), and P4 (feed with 12 ml/kg probiotic). The fish used were Nile tilapia (Oreochromis niloticus) with an average length of 6.53±0.35 cm and an average weight of 2.28±0.02 g. Feed was given at 08:00 and 16:00 until satiation. Stocking density was 15 fish per container filled with 15 liters of water, and the maintenance lasted for 30 days. The feed used was commercial pellet feed supplemented with probiotics according to the treatment, containing 32% protein. The results showed that the addition of probiotics (Probio-7) had a significant effect (P<0.05) on Specific Growth Rate (SGR), Feed Conversion Ratio (FCR), and Survival Rate (SR). Treatment P4 had the highest SGR value of 2.08±0.03 g, the lowest FCR of 0.33±0.02, and the highest Survival Rate (SR) of 84±7%. Keywords: Feed Conversion Ratio; Tilapia; Probiotics; Survival Rate